Exploring the user's preferences of different adaptation policies in adaptive menu design - Prashant Poudel; Sushil Shrestha (Trends in Computer Science and Information Technology - Peertechz Publications, 2023)
Adaptive User Interfaces (AUIs) have been developed to improve the usability of products by adapting to the user, the platform, and the environment. However, there is a limited understanding of how different adaptation policies impact personalization and usability in adaptive menus. The present study aimed to investigate the effectiveness of different adaptation policies in adaptive menu design. The study surveyed computer science students at Kathmandu University and conducted a usability study to gather data. The results of the study showed that a majority of participants were neutral in their perception of the ease of use of the websites they regularly visit, but a strong majority (83%) indicated a preference for personalized menu options. Personalization was found to be a key factor in the effectiveness of adaptive menus. Participants valued the ability of adaptive menus to tailor their options based on their specific needs or preferences. The findings of this study provide insight into users' preferences for adaptation policies in adaptive menus and suggest that a recency-frequency-based menu is most effective in meeting users' needs. Similarly, findings also suggest users' preference for adaptation policy also changes based on the context of use. Future research could further investigate the effectiveness of different adaptation policies in different contexts of use.